(untitled) (Quest Journal of Management and Social Sciences, 2020)
Background: Street vending, like other informal activities, contributes to employment generation. For many people, it is a source of income and thus has a poverty implication for street vendors. Objective: The major objective of this study is to analyze the poverty implication of street vending in the Kathmandu Valley, Nepal. The specific objectives are: to measure the net business income of street vendors, to determine factors influencing street vendors’ net business income and to analyze the poverty implication of street vending in the Kathmandu Valley. Methods: The study was based on the analytical approach, where the net business income of street vendors was measured, factors influencing net business income of street vendors were determined and the potential role of street vending on poverty reduction in Kathmandu Valley was analyzed. Factors influencingnet business income of street vendors were identified by applying regression analysis. For this, cross-sectional data were collected from randomly selected 450 street vendors of five locations of the Kathmandu Valley, i.e. Balaju, Lagankhel, Kalanki, Ratnapark and Suryabinayak. Data were collected using a structured questionnaire.The poverty implication of street vending was analyzed by using the consumption approach, wheremeasurement was done about whetherconsumption ofstreet vendors, which was covered by their net business income, was above the poverty line of the Kathmandu Valley. Results: Average monthly net business income of street vendors was Rs 22,500. Educational level, experience, sales and working hours per day were the factors influencing net business income of street vendors. 54% ofstreet vendors were found to have consumption above the poverty line which was covered by their net business income. Furthermore, it was found that if respondents were not involved in street vending; only 42% of respondents could have consumption above the poverty line which could be covered by their income from other jobs/professions. Conclusions: The study concludes that majority of people, who dostreet vendingin the Kathmandu Valley,come from low income family background. Street vending plays an important role to provide employment to the people belonging to socially and economically marginalized groups of the society.However, at the same time, street vendingalso creates problems like overcrowding on the roadsides, environmental pollution due to the generation of wasteduring street vending, and so on. So,the focus should be on shifting street vendors to the formal sectors in the long-term. Implications: As street vending is a source of income for thousands of socially and economically mariginalized groups and has poverty implications, it should not be viewed just as a problem of the street. If it is managed properly, it contributes tothe livelihood of thousands of people and provides goods and services at a cheaper price to low-income consumers.